2018
DOI: 10.1111/jan.13561
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for digital intervention for effective health promotion of small children—A cluster randomized trial

Abstract: The results from this study will make it possible to determine whether this new method can be recommended for implementation in child health clinic settings to support the participation of families with small children in promoting their health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 71 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…The study was designed as a two-arm cluster, randomised, controlled trial with a 4-month follow-up. A detailed research study protocol was previously published (Pakarinen et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study was designed as a two-arm cluster, randomised, controlled trial with a 4-month follow-up. A detailed research study protocol was previously published (Pakarinen et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the WellWe intervention followed the mediating variable model (Baranowski et al, 1997). The detailed description of the mediating variable model and the development process of the WellWe intervention (Pakarinen et al, 2018) and usability testing of the intervention (Pakarinen et al, 2017a) have been reported in previous publications.…”
Section: Interventionmentioning
confidence: 99%
See 3 more Smart Citations